Corduroy - Freeman, Don, 1908-1978. (New York : Viking Press, 1968)
A toy bear in a department store wants a number of things, but when a little girl finally buys him he finds what he has always wanted most of all.
Accelerated Reader AR
Keywords: Teddy bears -- Fiction; Toys -- Fiction; Fantasy; Picture books